Pengaruh Media Tanam dan Pupuk Organik Cair Limbah Kulit Pisang terhadap Pertumbuhan dan Produksi Tanaman Tomat (Lycopersicum esculentumMill.)secara Hidroponik Substrat - Siska Lian Fitariany; Ardian Ardian; Isnaini Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This study aims to determine the effect of husk and cocopeat charcoal planting medium, liquid organic fertilizer (POC) on banana peel waste and the interaction between planting medium and POC on banana peel waste on the growth and production of tomato plants cultivated in hydroponic substrates. This 1. Mahasiswa Fakultas Pertanian Universitas Riau 2. Dosen Fakultas Pertanian Universitas Riau JOM Faperta UR Vol. 6 Edisi 1 Januari s/d Juni 2019 research was conducted at the experimental field of Faculty of Agriculture University of Riau from August 2017 to January 2018 using factorial randomized complete design (CRD). The first factor was the planting medium consisting of two levels, husk charcoal (M1) and cocopeat (M2). The second factor was four concentrations of liquid organic fertilizer from banana peel waste consisting, without the administration of liquid organic fertilizer banana peel waste (P0), 2 ml.l-1 water (P1), 4 ml.l-1 water (P2) and 6 ml.l-1 water (P3). The parameters observed were plant height, day of flowering, number of flowers, percentage of fruit formation, day of first harvest, number of fruits per plant, total weight of fruit per plant and weight per fruit. The results showed that there was no interaction between the planting medium and the POC of banana peel waste as well as the single factor of POC peel waste waste on all observed treatments. The treatment of planting medium had a significant effect on all parameters observed except the percentage of fruit formation, age of first harvest, and weight per fruit. The use of husk charcoal medium produced higher plants with higher number of flowers, higher fruit weight and total fruit weight per plant compared to the use of cocopeat planting medium in the production of hydroponic substrate tomato plants. Keyword: tomatoes, planting medium, liquid organic fertilizer banana skin waste.